Owning your emotions or sentimental navel-gazing: Digital storytelling with South African pre-service student educators - Gachago Daniela; Ivala Eunice; Chigona Agnes; Condy Janet (Cultural Science)
Literature argues that for post-conflict pedagogies to facilitate student engagement across difference it requires emotional engagement with the subject. However, how to achieve such emotional engagement, without falling into the trap of sentimentality, is an area that is under-researched. This paper reflects on conversations with South African students in a final year pre-service teacher-training programme, who developed digital stories as a vehicle for student engagement across difference. Applying ‘critical emotional reflexivity’ (Zembylas 2011) as an analytical framework, we found that students described the digital storytelling process as opening up different ways of being with/for the ‘Other’ and allowing them to start questioning cherished beliefs and assumptions about the ‘Other’. However, they had difficulties in placing themselves in a bigger historical and sociocultural context. Furthermore, the specific set-up of the project made it difficult to track lasting social change within students, the fourth element of Zembylas’ theoretical framework. Findings also confirmed the potential of digital stories to lead to sentimentality and ‘passive empathy’ (Boler 1999), characterised by pity from the part of the privileged observer and resentment from the subjugated storyteller. We recommend adding a historical-political analysis of previous students’ stories to the digital storytelling process in order to help students deconstruct positions premised on the existence of clearly differentiated identities and to consciously create spaces where a reflection on the emotions students encountered while sharing and listening to their stories can be facilitated.